Divulgar o bem faz bem? Efeito do disclosure de responsabilidade social corporativa no desempenho da firma - Borges Junior, Dermeval Martins (2020)
The objective of this study is to examine the relationship between corporate social responsibility (CSR) disclosure and firm's performance, considering the specificities of the CSR dimensions, as well as the disclosure tone. Thus, the study advances by providing evidence of the effect that the publication of environmental, social and economic information has on performance metrics, especially when addressing the influence of the optimistic or pessimistic perspective employed in corporate reporting has on profitability, firm value and cost of capital. Another contribution of this study is the proposition and application of an original dictionary as an instrument for measuring CSR disclosure. The final sample included financial data, collected from Economatica database, and 1,797 corporate reports, obtained from GRI and CVM databases, from 219 different Brazilian public companies in the period from 2010 to 2019. The data were analyzed using descriptive statistics and regression models with panel data. The results of this research innovate by documenting that the prevalence of optimistic CSR information presented in the reports implies better rates of return and market value, as well as a reduction in the cost of capital. Another innovation for the literature based on the findings is that the influences on performance, arising from the dissemination of the different dimensions of CSR are not homogeneous. Thus, the conclusions of this research demonstrate the need to consider the disclosure tone and CSR topics when assessing the CSR disclosure and its effect on performance, advancing in relation to studies that are based on observation of the publication or not of a certain report or subject in the documents.